Income share of the top 10 %, the middle 50 % and the bottom 40 % in Latin America: 1920-2011 - Pablo Astorga (European Historical Economics Society (EHES), 2023)
This paper analyses, for the first time, comparable income shares of the top 10%, the middle 50% and the bottom 40% of the labour force in Argentina, Brazil, Chile, Colombia, Mexico and Venezuela (LA6) from 1920 to 2011 using a new dataset. The main findings are: i) over the whole period the LA6 exhibited a recurrent very high income concentration at the top 10% (an average share of 48.1%) and a relatively low share for those of the bottom 40% (13.9%), with a Palma ratio of 3.5; ii) although the three shares varied over time and showed important differences across countries and developmental epochs, the region largely missed the Great Levelling experienced by the US and the UK during the middle decades of the last century; iii) there is no support over time for the 'Palma proposition' stating a relative stability of the income share of the middle 50%. Despite policy efforts in the 2000s to raise the income of the bottom 40%, altogether, a more equitable income distribution is still a pending task in Latin America.
Keywords: O10; N1; O15; O54; 330; economic development; industrialisation; income inequality; LatinAmerica